A Low‐Temperature, Solution‐Processable Organic Electron‐Transporting Layer Based on Planar Coronene for High‐performance Conventional Perovskite Solar Cells. Issue 48 (9th November 2016) - Zhu, Zonglong; Xu, Jing‐Qi; Chueh, Chu‐Chen; Liu, Hongbin; Li, Zhong'an; Li, Xiaosong; Chen, Hongzheng; Jen, Alex K.‐Y.
Abstract : A low‐temperature, solution‐processable organic electron‐transporting material (ETM) is successfully developed for efficient conventional n‐i‐p perovskite solar cells (PVSCs). This ETM can show a high efficiency over 17% on rigid device and 14.2% on flexible PVSC. To the best of our knowledge, this efficiency is among the highest values reported for flexible n‐i‐p PVSCs with negligible hysteresis thus far.